REINTERPRETASI KONSEP WAKAF MENUJU PENGEMBANGAN WAKAF PRODUKTIF (UIN Sunan Kudus, 2015)
Endowments to save a great potential to be developed into a productive asset, which in the end was not only able to support socio-religious services, but also directed to support the various initiatives and social justice objectives. However, during this endowment has not played a significant role in realizing the benefit, the welfare of the people and social justice. Often heard slogan that endowments can be empowered to address issues of poverty, underdevelopment, poor nutrition, and so on. But there is no clear conceptual framework of how endowments can be developed to be an effective instrument for social change toward a more guarantee the welfare and justice. Abdullah Ahmad an-Na’im proposes transformation and reviewing their philanthropic tradition, in order to develop socio-economic communities, promote the fulfillment of human rights, political administration of justice, and guarantee the autonomy of the community. In addition to an-Na’im proposed above, there are several strategies in the development of productive endowments, among which are: the development of productive endowments through a reinterpretation of the concept of waqf, endowments regulatory legislation, issuance of certificates of endowment money, and productive waqf fund raising strategy.